New methods in diagnostic and therapy Coaxial telescopic catheters systems in percutaneous diagnostic and therapeutic procedures - Smolka, Grzegorz; Żurek, Przemysław; Peszek-Przybyła, Ewa; Twardowski, Romuald; Ochała, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
There are descriptions of the use of so-called telescopic systems in the literature concerning technical aspects of percutaneous therapeutic interventions within the heart or peripheral vessels. Those systems have either been built ad hoc, out of available instruments, or created as combined systems designed for such applications, which opens an opportunity to perform that kind of intervention in complicated anatomic systems. In the present paper the authors present application of telescopic systems in several areas of percutaneous interventions. The first includes coronary vessels in cases of additional anatomic complications such as significant aortic dilatation or very tortuous form of abdominal and thoracic aorta. Another area of application of telescopic systems includes peripheral vessels. As an example the authors describe procephalic and subclavian artery procedures here. The third area of interventions described in this article, where telescopic systems are applied, includes cases of structural heart diseases. The authors describe here the use of double and triple telescopic systems during procedures in patients with paravalvular (paramitral and para-aortal) leaks, as well as application of the above mentioned technique for passing a post-infarct ventricular septum defect. The discussion contains a presentation of previous reports on application of telescopic systems in various clinical situations, as well as limitations related to this method.